Population genetic structure and patterns of hybridization of the rare Lupinus tidestromii and its congener L. chamissonis (Fabaceae) inform seed sourcing strategies for population augmentation and reintroduction - Aspen Workman; Eleanor A. Pardini; Lorraine S. Parsons; Stefan G. Michalski; Tiffany M. Knight; Walter Durka (Conservation Genetics, 2026)
Human activities can impact the genetic diversity of populations, making them more vulnerable to extinction. Rare species are at an increased risk of negative genetic consequences of human activities, but understanding genetic diversity in rare species requires comparison to more common congeners. Hybridization, a common phenomenon in plants, can provide genetic rescue of genetically depauperate populations or put rare species at risk of being “swamped” out of the population. Human-mediated dispersal can create novel sympatry between previously allopatric species, fostering hybridization. The endangered Tideström’s lupine ( Lupinus tidestromii Greene ), endemic to the coastal dune ecosystem of California, co-occurs and hybridizes with the more common dune bush lupine ( L. chamissonis Eschsch .). We characterized 532 individuals from sympatric and non-sympatric sites across both species’ entire geographic ranges using genotyping-by-sequencing technology to identify 1,377 single-nucleotide polymorphisms. We analyzed population structure, genetic diversity within and among populations, and hybridization between L. tidestromii and L. chamissonis . Genetic diversity was lower in L. tidestromii than in the more common L. chamissonis . Both species showed strong population structure which coincided with a deep intraspecific split between populations north and south of San Francisco. Hybridization was confirmed at all sites of co-occurrence. Evidence of hybridization at multiple non-sympatric sites indicated former co-occurrence and recent local extirpations. From these results, we make specific management recommendations for L. tidestromii . Seeds from large populations in the north can be used to augment the smaller populations in this region and to reintroduce this endangered species back to extirpated sites. Our results highlight how studies considering spatial patterns of genetic diversity, hybridization and private alleles can be used to make clear recommendations for conservation actions.

A Robust Decision-Making approach to evaluating state support for nuclear programmes under uncertainty: A UK case study - J. Mangin; M. Bluck; G. Darch; D. Roberts; S. Brown; M. Workman (Energy Policy, 2025)

Interdisciplinary challenges for wildfire futures - T.A. Fairman; J. Aryal; P.J. Baker; A. Best; J. Cawson; H. Clarke; M.S. Fletcher; L. Gibbs; G. Foliente; L. Godden; M. Gibson; L. Kelly; et al. (Environmental Science & Policy, 2025)

Doing GOOD: Defining a green operational outcomes domain for nitrogen use in New York corn silage production - Agustin J. Olivo; Olivia F. Godber; Kirsten Workman; Karl Czymmek; Kristan F. Reed; Daryl V. Nydam; Quirine M. Ketterings (Field Crops Research, 2025)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

US adults accurately assess Hadza and Tsimane men's hunting ability from a single face photograph - Adar B. Eisenbruch; Kristopher M. Smith; Clifford I. Workman; Christopher von Rueden; Coren L. Apicella (Evolution and Human Behavior, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Analog-sensitive Cdk1 as a tool to study mitotic exit: protein phosphatase 1 is required downstream from Cdk1 inactivation in budding yeast - Jason M. Keaton; Benjamin G. Workman; Linfeng Xie; James R. Paulson (Chromosome Research, 2023)

A dynamic in vitro developing testis model reflects structures and functions of testicular development in vivo - Susanna Wegner; Tomomi Workman; Julie Juyoung Park; Sean Harris; James Wallace; Ian Stanaway; Sungwoo Hong; Brad Hansen; William C. Griffith; Elaine M. Faustman (Reproductive Toxicology, 2023)

Implementation During a Pandemic: Findings, Successes, and Lessons Learned from Community Grantees - Wilhelmenia Mathias; Karen A. Nichols; Jewel Golden-Wright; Ciaran M. Fairman; Tisha M. Felder; Lauren Workman; Karen E. Wickersham; Kimberly J. Flicker; Jingxi Sheng; Samuel B. Noblet; Swann Arp Adams; Jan M. Eberth; et al. (Journal of Cancer Education, 2023)

Alteration of oral microbiome composition in children living with pesticide-exposed farm workers - Ian B. Stanaway; James C. Wallace; Sungwoo Hong; Carly S. Wilder; Foad H. Green; Jesse Tsai; Misty Knight; Tomomi Workman; Eric M. Vigoren; Marissa N. Smith; William C. Griffith; Beti Thompson; et al. (International Journal of Hygiene and Environmental Health, 2023)

Understanding Quality Paradigm Shifts in the Evolving Pharmaceutical Landscape: Perspectives from the USP Quality Advisory Group - Jane Weitzel; Horacio Pappa; Gregory M. Banik; Amy R. Barker; Elizabeth Bladen; Narendra Chirmule; Joseph DeFeo; Jennifer Devine; Steven Emrick; Taha Kass Hout; Michael S. Levy; Gugu N. Mahlangu; et al. (The AAPS Journal, 2021)
Recent changes in the pharmaceutical industry have led to significant paradigm shifts in the pharmaceutical quality environment. Globalization of the pharmaceutical industry, increasingly rapid development of novel therapies, and adoption of new manufacturing techniques have presented numerous challenges for the established regulatory framework and quality environment and are impacting the approaches utilized to ensure the quality of pharmaceutical products. Regulators, industry, and standards-setting organizations have begun to recognize the need to rely more on integrated risk-based approaches and to create more nimble and flexible standards to complement these efforts. They also increasingly have recognized that quality needs to be built into systems and processes throughout the lifecycle of the product. Moreover, the recent COVID-19 crisis has emphasized the need to adopt practices that better promote global supply chain resilience. In this paper, the USP Quality Advisory Group explores the various paradigm shifts currently impacting pharmaceutical quality and the approaches that are being taken to adapt to this new environment. Broad adoption of the Analytical Procedure Lifecycle approach, improved data management, and utilization of digital technologies are identified as potential solutions that can help meet the challenges of these quality paradigm shifts. Further discussion and collaboration among stakeholders are needed to pursue these and other solutions that can ensure a continued focus on quality while facilitating pharmaceutical innovation and development.

When histones are under glucose starvation - Jaehyoun Lee; Seunghee Oh; Susan M Abmayr; Jerry L Workman (Journal of Biosciences, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Pediatric cancer knowledge: Assessment of knowledge of warning signs and symptoms for pediatric cancer among Brazilian community health workers - Gloria M. Workman; Raul C. Ribeiro; Shesh N. Rai; Arli Pedrosa; Don E. Workman; Francisco Pedrosa (Journal of Cancer Education, 2007)

DNA microarray analysis of fim mutations in Escherichia coli - M. Schembri; D. Ussery; C. Workman; H. Hasman; P. Klemm (Molecular Genetics and Genomics, 2002)

North American Agroforestry: An Integrated Science and Practice. H. E. Garrett, W. J. Rietveld and R. F. Fisher (eds.). American Society of Agronomy, Inc. Madison, WI, USA. - S. W. Workman; N. V. Thevathasan; A. M. Gordon (Agroforestry Systems, 2002)

Biphasic Material Properties of Lytic Bone Metastases - Cari M. Whyne; Serena S. Hu; Kimberly L. Workman; Jeffrey C. Lotz (Annals of Biomedical Engineering, 2000)

Specificity of induced resistance in the tomato, Lycopersicon esculentum - Michael J. Stout; Kathi V. Workman; Richard M. Bostock; Sean S. Duffey (Oecologia, 1997)

Urinary tract infections in primary biliary cirrhosis and other chronic liver diseases - J. O'Donohue; M. R. Workman; N. Rolando; M. Yates; J. Philpott-Howard; R. Williams (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Ute Russet: An oblong Russet potato cultivar with resistance to leafroll net necrosis andSclerotium rolfsii - D. G. Holm; J. A. Twomey; M. Workman (American Journal of Potato Research, 1987)

Potato clone variation in blackspot and soft rot susceptibility, redox potential, ascorbic acid, dry matter and potassium - M. Workman; D. G. Holm (American Journal of Potato Research, 1984)

Sangre: An oval, high quality red potato - J. A. Twomey; J. J. Pavek; D. G. Holm; M. Workman; D. L. Corsini (American Journal of Potato Research, 1982)

The effect of storage environment on the infection of potato tubers byAlternaria solani - E. C. Nnodu; M. D. Harrison; M. Workman (American Journal of Potato Research, 1982)

Pre-harvest burning for control of tuber infection byAlternaria solani - L. K. Lahman; M. D. Harrison; M. Workman (American Journal of Potato Research, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Effects of soil fumigation with Telone C on soil and plant nitrogen, verticillium wilt and yield of Norland and Norgold potatoes - M. Workman; M. D. Harrison; C. H. Livingstone (American Journal of Potato Research, 1977)

The effect of storage factors on membrane permeability and sugar content of potatoes and decay byErwinia carotovora var.atroseptica andFusarium roseum var.Sambucinum - M. Workman; E. Kerschner; M. Harrison (American Journal of Potato Research, 1976)

The influence of storage factors on endogenous ethylene production by potato tubers - D. L. Creech; M. Workman; M. D. Harrison (American Journal of Potato Research, 1973)

Oromonte, a chipping potato for Colorado - J. A. Twomey; R. V. Akeley; K. W. Knutson; M. Workman (American Journal of Potato Research, 1968)